Polygonatum Polysaccharide Regulates Macrophage Polarization and Improves LPS-Induced Acute Lung Injury through TLR4-MAPK/NF-κB Pathway - Weizheng Zhou; Jiang Hong; Tao Liu; Mengxing Li; Hai Jin; Xiaowei Wang (Canadian Respiratory Journal)
Objective. To investigate the effects of polygonatum sibiricum polysaccharides (PSPs) on the polarization of macrophages to M1 and M2 phenotypes and their potential mechanism. Methods. PSPs samples were prepared through water extraction and alcohol precipitation assay. The properties of PSPs were identified and analyzed by high-performance liquid chromatography, FT-IR, and NMR assay. Then, the effects of PSPs on mouse macrophage RAW264.7 viability were measured by CCK-8 assay. The cells were randomly divided into the control group, PSPs group, LPS group, and LPS + PSPs group. M1 phenotype polarization of RAW264.7 cells was induced by LPS treatment. The effects of various treatments on expression of M2 phenotype CD206, activation of TLR4-MAPK/NF-κB signal pathway, and translocation of NF-κB into the nucleus were determined by ELISA, western blot, and immunofluorescence assay, respectively. TLR4 inhibitor, TAK-242, and MAPK inhibitor, BIRB 796, were used to verify the effects of PSPs on the TLR4-MAPK/NF-κB pathway. The mice model of acute lung injury (ALI) was established and randomly divided into control group, PSPs group, LPS group, and LPS + PSPs group. Bronchoalveolar lavage fluid (BALF) and lung tissue were collected to measure protein, inflammatory cells, neutrophil and macrophage cells number, and the levels of IL-6 and TNF-α in BALF. Flow cytometry and western blot assay measured the phenotypic changes of macrophages and the activation of the TLR4-MAPK/NF-κB signaling pathway. Results. The concentrations of PSPs lower than 100 μg/mL showed no toxicity to RAW264.7 cells. PSPs treatment could significantly reverse the reduction of CD206 protein expression (P<0.05) and the increase of the expression of inflammatory factor TNF-α, IL-1β, and IL-6 (all P<0.05), TLR4-MAPK/NF-κB signaling pathway activation (all P<0.05), and NF-κB translocation into the nucleus induced by LPS. The effect of inhibitors TAK-242 and BIRB 796 was consistent with that of PSPs. In the mice model of ALI, PSPs treatment could reduce the total protein levels of BALF and the number of inflammatory cells level, reverse the number changes of neutrophils and macrophages, and downregulate the proinflammatory factors IL-6 and TNF-α caused by LPS (all P<0.05). In addition, PSPs treatment could also significantly reverse the increase in the number of iNOS expressing macrophages in alveolar lavage fluid induced by LPS (P<0.05). In contrast, CD206-expressed cells decreased (P<0.05). PSPs could also reverse LPS-induced TLR4-MAPK/NF-κB signal pathway protein activation (all P<0.05). Conclusion. PSPs could suppress TLR4-MAPK/NF-κB activation induced by LPS, inhibit M1 phenotypic polarization of macrophages, and promote M2 phenotypic polarization, thus playing an anti-inflammatory role.